Increasing Vocabulary Mastery Through Animals Video At Kindergarten PGRI Bulucenrana - Ismail Ma'sa; Andi Sadapotto; Hasriyani Y; Usman M (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2021)
The objective of the research was the find out whether or not of animal videos increases vocabulary mastery in PGRI Bulucenrana kindergarten students. This study uses an experimental design. The population of this research is one group, group B in TK PGRI Bulucenrana. In the academic year 2018/2019 with a total population of 12 students. The sample of this study was 12 students. The sample of this study was 12 students or a total sample. This study used media animals video in class. Researchers found that the use of animal videos can increase vocabulary mastery in Bulucenrana PGRI kindergarten students. The average value of the initial test (21,08) is lower than the average value of the final test (77,50), it is also evidenced by the P-Value (0,000 < 0,05) a significant level of 0,05. So the researchers concluded that H0 was rejected and H1 was accepted. Based on data analysis, the researcher concludes that: animals video media is effective in increasing vocabulary mastery in Bulucenrana PGRI kindergarten students